Methodology for Flow Cytometric Analysis of Dendritic Cell Subsets in Pregnant Women with Early Onset Pre-eclampsia - Sundararajan, Aarthi; Jain , Rohit; Vora , Kranti; Natesan , Senthilkumar; Vaidya, Vidhi (New Advances in Medicine and Medical Science Vol. 2, 2023)
Pre-eclampsia (PE) is a pro-inflammatory disease associated with pregnancy. The only known remedy is to deliver the fetus and placenta. Hypertension and proteinuria after the 20th week of pregnancy are clinical indicators of PE. Early onset pre-eclampsia (EOPE), a severe variant of PE, is defined as clinical signs appearing before 34 weeks of pregnancy. Human dendritic cell (DC) subtypes (CD1c+, CD141+ myeloid DCs, and plasmacytoid DCs) are intricately implicated in the inflammatory process and are considerably changed in a variety of proinflammatory illnesses. These alterations provide value for monitoring DC subsets as potential biomarker(s) and as targets for immunotherapeutic treatment. The main objective of the study is to delineate how the three DC subsets are altered quantitatively and functionally in blood and decidua of EOPE patients, compared to normal pregnant women. DC subsets play an important role in normal pregnancy by facilitating effective trophoblast migration and invasion and establishing an anti-inflammatory milieu of immunotolerance. In contrast, a detailed examination of the makeup and function of DC subsets in the proinflammatory milieu of EOPE pregnancy is required. In this regard, the developed methodology examines how DC subsets differ (quantitatively and functionally) in EOPE patients versus normal pregnant women. The multiparametric flow cytometry method is used to determine alterations in the profile of DC subsets in the blood and decidua of EOPE patients. Normal pregnant women are included as controls. Identifying possible biomarkers will be based on an understanding of alterations in the profile of DC subsets in blood samples from EOPE patients. The basis for creating innovative immunotherapeutic techniques targeting various DC subsets or their products for the treatment of EOPE will similarly be variations in the profile of DC subsets in the decidua of EOPE patients. Overall, the methodology will support the development of future large-scale, prospective clinical trials with a focus on developing approaches for the early detection and treatment of EOPE in pregnant women.